Temporal modulation transfer functions for band-limited noise in subjects with cochlear hearing loss - Moore, B C; Shailer, M J; Schooneveldt, G P (British journal of audiology, 1992)
The modulation depth required for the detection of sinusoidal amplitude modulation was measured as a function of modulation rate, giving temporal modulation transfer functions (TMTFs). The carrier was a one-octave wide noise centred at 2 kHz, and it was presented in an unmodulated background noise lowpass filtered at 5 kHz. Three subjects with unilateral cochlear hearing loss were tested. For each subject, the normal ear was tested both at the same sound pressure level (SPL) and at the same sensation level (SL) as the impaired ear. The TMTFs were essentially the same for the normal and impaired ears, both at equal SPL and at equal SL. The better ears of three subjects with bilateral cochlear losses were also tested. Again, TMTFs were essentially the same as obtained for normal ears. These results suggest that temporal resolution is not necessarily adversely affected by cochlear hearing loss, at least as measured by this task.